Pornography Use, Two Forms of Dehumanization, and Sexual Aggression: Attitudes vs. Behaviors. Issue 6 (18th August 2021) - Zhou, Yanyan; Liu, Tuo; Yan, (Harry) Yaojun; Paul, Bryant
Abstract: Sexual objectification is a common pornographic theme. Research shows that sexual objectification leads to the expression of aggressive attitudes and behaviors toward women. Based on a survey study of 320 male participants, this study re-conceptualizes sexual objectification in terms of two forms of dehumanization. Evidence suggests men's pornography use is positively associated with both forms, but mechanistic dehumanization of women is more associated with aggressive attitudes while animalistic dehumanization is more associated with aggressive behaviors. Findings indicate how objectifying pornography use may relate to aggressive attitudes and behaviors and inform the future education campaigns and interventions to reduce sexual aggression.